The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.2307/3079280
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Consequences of Asymmetric Dispersal Rates

Abstract: We study the consequences of asymmetric dispersal rates (e.g., due to wind or current) for adaptive evolution in a system of two habitat patches. Asymmetric dispersal rates can lead to overcrowding of the "downstream" habitat, resulting in a source-sink population structure in the absence of intrinsic quality differences between habitats or can even cause an intrinsically better habitat to function as a sink. Source-sink population structure due to asymmetric dispersal rates has similar consequences for adapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
149
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(156 citation statements)
references
References 0 publications
7
149
0
Order By: Relevance
“…In the absence of differences in survival, fecundity or extinction probabilities and even habitat quality, biased spore dispersal may generate directional gene flow (cf. Stanton et al, 1997;Kawecki and Holt, 2002). If the transport of spores and gametes occurs predominantly at low tide when small streams flow from high-to lower-shore pools, higher pools will be relatively isolated from gene flow compared to lower pools.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of differences in survival, fecundity or extinction probabilities and even habitat quality, biased spore dispersal may generate directional gene flow (cf. Stanton et al, 1997;Kawecki and Holt, 2002). If the transport of spores and gametes occurs predominantly at low tide when small streams flow from high-to lower-shore pools, higher pools will be relatively isolated from gene flow compared to lower pools.…”
Section: Discussionmentioning
confidence: 99%
“…Details of genetic architecture matter. For instance, for alleles of small effect, increasing bidirectional movement usually facilitates adaptation to a sink (83), but for alleles of large effect, intermediate rates of movement are least favorable for their retention (84,85).…”
Section: The Evolutionary Nichementioning
confidence: 99%
“…However, asymmetry in local adaptation provides potential pitfalls for researchers; habitat-induced asymmetry in dispersal may lead to com pletely asymmetrical adaptation, so that populations in two environments do not differ in genetic composition, but one is locally adapted and the other is maladapted (Ronce and Kirkpatrick 2001;Kawecki and Holt 2002). Under these conditions, standard tests for local adaptation, such as reciprocal transplant experiments or common garden experiments, would be unable to discriminate this from a failure of both populations to become locally adapted, because the populations are not genetically differentiated.…”
Section: Genetic Differentiation Local Adaptation and Speciationmentioning
confidence: 99%
“…Under these con ditions, the allele frequencies of propagules from higherquality environments can swamp the frequency of alleles from lower-quality environments in both habitats. Ka wecki and Holt (2002) evaluated the effect of asymmetry in dispersal rate between two patches on the probability of fixation of alleles that were advantageous in one patch but disadvantageous in another. Under two different sets of genetic assumptions, they found that local adaptation was more likely to occur in the population with a higher emigration rate.…”
Section: Genetic Differentiation Local Adaptation and Speciationmentioning
confidence: 99%
See 1 more Smart Citation